Thermal conductivity of single-crystalline AlN. (11th June 2018) - Rounds, Robert; Sarkar, Biplab; Klump, Andrew; Hartmann, Carsten; Nagashima, Toru; Kirste, Ronny; Franke, Alexander; Bickermann, Matthias; Kumagai, Yoshinao; Sitar, Zlatko; Collazo, Ramón
Abstract: The thermal conductivity of AlN single crystals grown by physical vapor transport (PVT) and hydride vapor phase epitaxy (HVPE) was measured in the range of 30 to 325 K by the 3ω method. The measured room-temperature thermal conductivity ranged from 268 to 374 W m −1 K −1 . Higher thermal conductivity correlated with higher transparency at 265 nm and lower total impurity levels.